Reconstructing the Concept of Ahliyyah (Legal Capacity) for Autonomous AI Entities in Islamic Jurisprudence: A Critical Analysis of Digital Contracts and Muamalah Principles - Nasiri (STAI Syaichona Moh. Cholil Bangkalan, 2023)
The rapid advancement of Autonomous Artificial Intelligence (AI) has challenged the traditional human-centric framework of Ahliyyah (legal capacity) in Islamic jurisprudence. This study aims to investigate the legal status of AI entities in executing digital contracts and to propose a reconstruction of Ahliyyah that accommodates non-human autonomous agents. Using a qualitative-normative legal research method with a Maqashid al-Shari’ah approach, this study analyzes classical Fiqh texts alongside modern technological realities. The findings reveal that while AI lacks metaphysical consciousness (Ruh), it possesses